Pengaruh Aromaterapi Inhalasi Terhadap Penurunan Nilai Kecemasan Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa Di Rumah Sakit Grandmed Lubuk Pakam - Pratiwi Christa Simarmata; Sari Desi Esta Ulina Sitepu; Erik Huandi Sitorus (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Anxiety is one of the complaints of patients with Chronic Kidney Failure (CKD) undergoing hemodialysis. CAM (Complementary Alternative Medicine) therapy as a substitute for drugs using lavender aromatherapy is expected to reduce anxiety levels in CKD patients who are undergoing hemodialysis therapy. The aim of the study was to determine the effect of inhaled aromatherapy on reducing anxiety levels in CKD patients undergoing hemodialysis at Grandmed Lubuk Pakam Hospital. This type of research is quantitative research with a pre-experimental research design with one group pre-test and post-test approaches. The sampling technique in this study was total sampling with a total of 20 respondents. Data analysis was carried out using the sample paired t-test. The results of the study obtained a p-value of 0.00 where the p-value was <0.05, it can be concluded that there was a significant effect after being given inhaled aromatherapy to decrease anxiety values in CKD patients at Grandmed Lubuk Pakam Hospital. The conclusion in this study is that lavender inhalation aromatherapy has a significant effect on reducing anxiety levels in CKD patients undergoing hemodialysis and it is recommended for health workers to further improve anxiety management with non-pharmacological measures.